Current Situation and Countermeasures of Teaching Chinese Ancient Poetry - Zhao, Jiejing; Li, Yan (International Journal of Social Sciences and Public Administration, 2024)
The teaching of ancient poems occupies an important position in China's education system, which inherits the excellent traditional culture of the Chinese nation. However, the current teaching of ancient poetry faces some problems, such as the disconnection between the content of teaching materials and reality, the single teaching method, the lack of students' interest, and the teachers' low literacy in ancient poetry. In order to improve the teaching of ancient poetry, this paper puts forward corresponding countermeasures and suggestions. First of all, improve the teaching materials and curriculum, make them closer to the students' life reality, and increase the fun and practicality of ancient poems. Secondly, innovative teaching methods and means, such as the use of contextual teaching, interactive teaching, etc., in order to improve students' learning interest and participation. At the same time, to stimulate students' interest in learning and cultivate their love for ancient poems, so as to improve the effect of teaching ancient poems. Finally, improve the quality and training of teachers, strengthen teachers' understanding of ancient poetry and teaching ability, in order to improve the overall quality of teaching. By analyzing the current situation of teaching ancient poems, this paper puts forward targeted countermeasures and suggestions, aiming to provide reference for improving the current situation of teaching ancient poems in China.